Resting-state functional MRI reveals altered brain connectivity and its correlation with motor dysfunction in a mouse model of Huntington's disease. Issue 1 (December 2017) - Li, Qiang; Li, Gang; Wu, Dan; Lu, Hanbing; Hou, Zhipeng; Ross, Christopher; Yang, Yihong; Zhang, Jiangyang; Duan, Wenzhen
Abstract Huntington's disease (HD) is an autosomal dominant inherited neurodegenerative disorder, and no cure is available currently. Treatment of HD is likely to be most beneficial in the early, possibly pre-manifestation stage. The challenge is to determine the best time for intervention and evaluate putative efficacy in the absence of clinical symptoms. Resting-state functional MRI may represent a promising tool to develop biomarker reflecting early neuronal dysfunction in HD brain, because it can examine multiple brain networks without confounding effects of cognitive ability, which makes the resting-state fMRI promising as a translational bridge between preclinical study in animal models and clinical findings in HD patients. In this study, we examined brain regional connectivity and its correlation to brain atrophy, as well as motor function in the 18-week-old N171-82Q HD mice. HD mice exhibited significantly altered functional connectivity in multiple networks. Particularly, the weaker intra-striatum connectivity was positively correlated with striatal atrophy, while striatum-retrosplenial cortex connectivity is negatively correlated with striatal atrophy. The resting-state brain regional connectivity had no significant correlation with motor deficits in HD mice. Our results suggest that altered brain connectivity detected by resting-state fMRI might serve as an early disease biomarker in HD.